2013
DOI: 10.2174/1573400511309010013
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver Burden in Fragile X Families

Abstract: Complex caregiving issues occur in multigenerational families carrying the fragile X mutation and premutation. The same family members may care for children or siblings with fragile X syndrome (FXS) and for elderly parents with fragile X-associated tremor/ataxia syndrome (FXTAS). Family caregivers experience anxiety, depression, neglect of personal health care needs, employment difficulties, and loss of social support, leading to isolation and further psychiatric consequences. There is growing awareness of car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 56 publications
(66 reference statements)
0
1
0
Order By: Relevance
“…There has been relatively limited research on the impact on the family of having a child with a neurogenetic condition. It has been suggested that in FXS, caregivers may experience anxiety, depression, neglect of personal health, employment difficulties and loss of social support (Iosif et al 2013) and increased financial burden (Ouyang et al 2010). Parents of children with WS have been found to display more pessimism than parents of children with Down syndrome and the strongest predictor of family problems in the syndrome was younger age and problem behaviors (Fidler et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…There has been relatively limited research on the impact on the family of having a child with a neurogenetic condition. It has been suggested that in FXS, caregivers may experience anxiety, depression, neglect of personal health, employment difficulties and loss of social support (Iosif et al 2013) and increased financial burden (Ouyang et al 2010). Parents of children with WS have been found to display more pessimism than parents of children with Down syndrome and the strongest predictor of family problems in the syndrome was younger age and problem behaviors (Fidler et al 2000).…”
Section: Introductionmentioning
confidence: 99%